Enforcement actions on banks and the structure of loan syndicates - Delis, Manthos D.; Iosifidi, Maria; Kokas, Sotirios; Xefteris, Dimitrios; Ongena, Steven (Journal of Corporate Finance, 2020)
We investigate the effect of regulatory enforcement actions on banks' reputation by estimating the effect of non-compliance with laws and regulations among lead arrangers on the structure of syndicated loans. Consistent with a regulatory reputational stigma, a punished lead arranger increases her loan share to entice participants to continue to co-finance the loan. Consequently, when punished lead arranger initiates a new syndicated loan, then this loan tends to be more concentrated and co-funded by participants with previous collaboration with the lead arranger. However, the observed share increases by punished lead arrangers are seemingly mitigated by extending the loan guarantees, performance pricing provisions, and covenants.